2020
DOI: 10.1016/j.esxm.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sexual Disorders in Patients With Rheumatoid Arthritis and Associated Factors

Abstract: Introduction Rheumatoid arthritis (RA) is a chronic and progressive pathology, present in between 0.5% and 1% of adults. Sexual disorders (SDs) occur in between 31% and 70% of all patients with RA. Aim To establish the associated risk factors and the prevalence of SDs in a group of patients with RA. Methods An analytical cross-sectional study was performed, evaluated with the Diagnostic and Statistical Manual of Mental Disorders-V tool. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
2
3
1
Order By: Relevance
“…A newly published study found sexual dysfunction to be prevalent in one-third of patients with RA, and gender, age above 50 years, disease activity, mental health, and cohabitation were among factors associated with sexual dysfunction. 34 The present study found no significant association between sexual dysfunction and disease activity (measured with the HAQ) or cohabitation. However, significant associations were present between general questions about sex life and disease activity, depression, loneliness, and alcohol consumption.…”
Section: Discussioncontrasting
confidence: 82%
“…A newly published study found sexual dysfunction to be prevalent in one-third of patients with RA, and gender, age above 50 years, disease activity, mental health, and cohabitation were among factors associated with sexual dysfunction. 34 The present study found no significant association between sexual dysfunction and disease activity (measured with the HAQ) or cohabitation. However, significant associations were present between general questions about sex life and disease activity, depression, loneliness, and alcohol consumption.…”
Section: Discussioncontrasting
confidence: 82%
“…Of relevance, each definition was also differentiated from the other one by specific contents (such as risks and consequences for/of sexual-related diseases for SH, and the family project life stage associated for RH), which might be threatened by the underlying rheumatic disease. Our results are in accordance with a recent systematic review and meta-analysis, 5 which demonstrated that RA diagnosis had a significant and negative impact on female sexual function, 26 which has been corroborated in patients from the Latin American region 16 . Similar results had been observed in qualitative studies that highlighted SH was affected in RA females 27 and in patients with rheumatic diseases from both sexes, highly represented by RA patients 27 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with a recent systematic review and meta-analysis, 5 which demonstrated that RA diagnosis had a significant and negative impact on female sexual function, 26 which has been corroborated in patients from the Latin American region. 16 Similar results had been observed in qualitative studies that highlighted SH was affected in RA females 27 and in patients with rheumatic diseases from both sexes, highly represented by RA patients. 27 Further on, there is evidence that fear of being abandoned by the partner is an emotional experience due to RA and can decrease sexual activities.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Without early diagnosis and treatment, the disease may result in progressive disability and damage to multiple organs [ 2 ]. Limitations associated with the disease, both physical and psychological, may affect patients’ sex lives [ 3 ]. RA can affect sexual function in various ways, including pain, joint stiffness and swelling, chronic fatigue, and limitations in activities of daily living [ 4 ].…”
Section: Introductionmentioning
confidence: 99%